The Effectiveness of Letrozole-Electroacupuncture Adjuvant Therapy in Reducing Resistance and Pulsatility Indices in Women with Polycystic Ovarian Syndrome - Octavia, Dhamayanti Eka; Budihastuti, Uki Retno; Melinawati, Eriana; Anggraini, Nutria Widya Purna; Yuliantara, Eric Edwin; Nurwati, Ida; Hadi, Cahyono (Journal of Maternal and Child Health, 2020)
Background: Polycystic Ovarian Syndrome (PC